ETIKA PESERTA DIDIK DAN PENDIDIK MENURUT MUḤAMMAD NAWAWĪ AL-JĀWĪ (1230-1314 H/1813-1897 M) Studi Kitab Murāqu al-‘Ubūdiyyah Syarḥ Bidāyah al-Hidāyah - Erik Suwandinata (Hijri, 2017)
The aims of the research are: 1) To find the ethics of students by Muḥammad Nawawī al-Jāw‘s book, Murāqu al-‘Ubūdiyyah Syarḥ Bidāyah al-Hidāyah. 2) To find the ethics of teachers by Muḥammad Nawawī al-Jāw's book. 3) To find the relevance Muḥammad Nawawī al-Jāw's thought about ethics of students and teachers with Islamic education currently. Type of the research is a literary research that find various sources related to Muḥammad Nawaw's thought about students and teachers. Furthermore, the primary of source is Murāqu al-‘Ubūdiyyah Syarḥ Bidāyah al-Hidāyah who written by Muḥammad Nawawī al-Jāwī. The secondary of sources are some books who written by him and scholars who talked about Muḥammad Nawawī al-Jāwī. The researcher used content analysis to analyze the data. The results of this research are: First, Muḥammad Nawawī al-Jāwī ever come studied in Indonesia and Hijaz/Mecca's teachers, and also a productive teacher and the author. Second, the contains of Murāqu al-‘Ubūdiyyah Syarḥ Bidāyah al-Hidāyah' book areethical issues of students and teachers. The ethics of students related to: 1) Personal ethics, 2) Learning’s ethics and teachers interacting, 3) Friends interacting. There are three ethics of the teachers: 1) Personal ethics 2) Teaching's ethics and students interacting. Third, the ethical theory Sheikh Nawawī has relevanced with modern education currently. The students's ethics compared of the 18 character values formulated by the Ministry of National Education, while the teacher's ethics compared with the four teacher competencies.